2014
DOI: 10.1002/chem.201405840
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Photoswitching of RNA Hybridization at Room Temperature with an Azobenzene C‐Nucleoside

Abstract: Photoregulation of RNA remains a challenging task as the introduction of a photoswitch entails changes in the shape and the stability of the duplex that strongly depend on the chosen linker strategy. Herein, the influence of a novel nucleosidic linker moiety on the photoregulation efficiency of azobenzene is investigated. To this purpose, two azobenzene C-nucleosides were stereoselectively synthesized, characterized, and incorporated into RNA oligonucleotides. Spectroscopic characterization revealed a reversib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 81 publications
7
76
1
6
Order By: Relevance
“…The conclusion that the βD-Azo/(AP) system exhibits the largest difference in structural stability between trans-and cis-azobenzene-tethered RNA at room temperature is in good agreement with our recent experimental findings. 25 It has been found by Asanuma et al 23 that a more effective photoswitching, entailing a larger difference in melting temperature between the trans and cis forms of RNA hybridization, is feasible for the DT linker without a moiety in the opposite strand but only at elevated temperature. It should also be noted that our previous results for an azobenzene in DNA with the LT linker and without any moiety in the opposite strand showed destabilization of DNA only at elevated temperature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The conclusion that the βD-Azo/(AP) system exhibits the largest difference in structural stability between trans-and cis-azobenzene-tethered RNA at room temperature is in good agreement with our recent experimental findings. 25 It has been found by Asanuma et al 23 that a more effective photoswitching, entailing a larger difference in melting temperature between the trans and cis forms of RNA hybridization, is feasible for the DT linker without a moiety in the opposite strand but only at elevated temperature. It should also be noted that our previous results for an azobenzene in DNA with the LT linker and without any moiety in the opposite strand showed destabilization of DNA only at elevated temperature.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the D-threoninol (DT) and Lthreoninol (LT) linkers have been introduced in refs 26 and 30, and the β-deoxyribose (βD) linker has been addressed in our recent work. 25 Figure 2 illustrates a βD-azobenzene substituted RNA duplex.…”
Section: Computational and Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[28] Recent studies have shown that even asmall change of the 2'-substituent of the azobenzene C-nucleosides influences the photo-controlled duplex (de)stabilization of DNA nanoarchitecture. Azobenzene photoswitches have been widely applied for photo-control of nucleic acids due to the different stacking properties of the (E)-and (Z)-azobenzene moiety.Especially, the azobenzene C-nucleosides show excellent photochemical behavior due to their ability to completely isomerize in both isomeric forms (E and Z)i naduplex even at room temperature.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…In a recent study, the hybridization of RNA was controlled with light by incorporating an azobenzene group into the structure of a ribose unit on the oligonucleotide strand [100]. The nitrogenous base was substituted for an azobenzene derivative (Figure 9.16).…”
Section: Controlling Rna Duplex Hybridization With Lightmentioning
confidence: 99%